The Impact of Inflation, Money Supply, and Sharia Third-Party Funds on the Sharia Monetary System, 2018–2024 - Lalu Kamala Hady; Muaidy Yasin; M Irwan (Jurnal Ekonomi Pembangunan, 2026)
This study aims to analyze the impact of inflation, money supply (M2), and Islamic third-party funds (DPKS) on Islamic monetary operations in Indonesia using the Vector Error Correction Model (VECM) approach. The data used consist of secondary time-series data obtained from official sources such as Bank Indonesia and the Financial Services Authority (OJK) for the period 2018–2024. The results indicate a long-term relationship among the study variables. In the long run, inflation and DPKS have a significant negative effect on Islamic monetary operations, while the money supply has no significant effect. In the short term, the adjustment process toward equilibrium proceeds relatively slowly, indicating that the Islamic monetary system tends to be stable and unresponsive to short-term shocks. Analysis of the Impulse Response Function (IRF) shows that the response to shocks is volatile at the beginning of the period but then stabilizes, while the Forecast Error Variance Decomposition (FEVD) results indicate that variations in the Islamic monetary system are dominated by internal factors. These findings underscore the importance of liquidity management and the optimization of intermediation functions in maintaining the stability of the Islamic monetary system.